Association between metabolic syndrome components and impulse control disorders in Parkinson’s disease - Chen, Linxi; He, Xinwei; Tao, Taotao; Chen, Linkao; Chen, Yun; Mao, Lingqun; Liu, Peng (Frontiers in Neuroscience, 2023)
Background Current evidence on management of impulse control disorders (ICDs) in Parkinson’s disease (PD) remains scarce, and exploring modifiable risk factors is crucial. Objective We evaluated the profiles of ICDs in PD patients and aimed to determine the associations between ICDs, metabolic syndrome components and other clinical features. Methods We enrolled patients diagnosed with PD in this study and conducted comprehensive clinical assessments. Results We recruited 39 PD patients with ICDs and 66 PD patients without ICDs. Out of the 39 patients with ICDs, 19 (48.7%) had one impulse control disorder, while 20 (51.3%) had two or more. The most commonly reported symptom of ICDs was compulsive eating (48.7%). Significant differences were observed between the PD patients with and without ICDs in terms of their HbA1c levels, history of diabetes mellitus, dopamine agonist use, levodopa equivalent dose of dopamine agonists (LED DA), and Hamilton Depression Rating Scale (HAMD) scores. HbA1c levels were significantly higher in the PD patients with compulsive eating. Stepwise logistic regression analyses were performed with the dependent variables of ICDs (yes/no) and compulsive eating (yes/no). Among the 105 PD patients, those with ICDs exhibited higher levels of HbA1c, HAMD score and LED DA than those without ICDs (p < 0.01). Among 39 PD patients with ICDs, those with compulsive eating exhibited higher levels of HbA1c (OR=2.148, 95% CI=1.004-4.594, p < 0.05). Among 105 PD patients, those with compulsive eating exhibited higher levels of HbA1c, LED DA and HAMD score (p < 0.05). Conclusions This study provides insights into the profiles of ICDs in PD patients and their associations with various clinical features. Compulsive eating was the most common ICD symptom reported. Notably, HbA1c levels were found to be higher in patients with compulsive eating, indicating poor blood glucose control as a potential risk factor for ICDs in PD. Further research is needed to confirm the modifiable risk factors for ICDs in PD.